Special Legal Regime of Agricultural Land, Forest Land and Grassland - Cătălina Georgeta Dinu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Certain categories of land have a special character and, consequently, a strict legal regime, regulated by various legal provisions whose application leads, indirectly, to a restriction of the right of private property for the owners. These limitations are imposed to protect the public interest, but it is important to find a fair balance between the interests of private owners and those of the community. Through this study we will investigate which are these limitations, at European level, respectively at national level.